2021
DOI: 10.35882/jeeemi.v3i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Apnea Monitor Using Pulse Oxymetry with Tactile Stimulation to Reduce Respiration Failure

Abstract: Respiratory failure (apnea) often occurs in premature babies, this should be avoided because it causes low oxygen concentrations in the blood so that it can damage brain function and lead to death. Apnea is characterized by a decrease in oxygen saturation (SpO2). The purpose of this study was to design an apnea monitor that was detected with SpO2 parameters, alarms, and vibrating stimulation. This study uses infrared and red LEDs that emit light through the surface of the finger and is detected by a photodiode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A conclusion may therefore be that improvements of the sensors and a more reliable attachment avoiding the slipping off the sensor during the night might be required. However, previous research has shown that finger sensors are typically more reliable in terms of motion artifacts than other types of sensors [1,2].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…A conclusion may therefore be that improvements of the sensors and a more reliable attachment avoiding the slipping off the sensor during the night might be required. However, previous research has shown that finger sensors are typically more reliable in terms of motion artifacts than other types of sensors [1,2].…”
Section: Discussionmentioning
confidence: 93%
“…A future feature worth investigating would also be the possibility not to set a certain threshold (such as 85%), but a percentage deviation from the baseline that would lead to the alarm. For example, Forra Wakidi et al suggested a 5% decrease in SpO2 value within 5 s from the baseline as indicative of apnea [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decade, there has been a considerable increase in interest and research activity in wearable sensors to measure blood oxygen saturation (SpO 2 ) [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%